Genetic-based personalized nutrition in Hungary – is there a viable business model? - Farkas, Noémi Dóra; Kiss, Marietta (Applied Studies in Agribusiness and Commerce, 2021)
A move from population-based nutrition guidance toward personalized nutrition may offer a more effective strategy than before to improve dietary habits of citizens worldwide. However, a significant number of consumers are not willing to adopt the highest level of personalization, i.e., gene-based personalized nutrition. The purpose of this paper is to examine whether there is a viable business model for genetically based personalized nutrition services in Hungary, and what business model would promote a higher level of consumer acceptance of the new technology. As a first step, a systematic Internet search was conducted to gather personalized nutrition counselling services that meet four criteria: they are related to nutrition; show some level of personalization; offer a product or service; and use some kind of consumer information to personalize a product or service. The second step was an expert content analysis of the service providers’ websites to identify the nine elements of the Business Model Canvas, based in which business model archetypes were identified. We can conclude that the vast majority of services available in the Hungarian market are based on phenotypic information; gene-based personalized nutrition is only rarely found. Our results suggest that business models of the Hungarian market differ significantly from the models identified by previous research. Of the eight identified business model archetypes, the “All in one place” model would promote a higher level of consumer acceptance of nutrigenomics-based services.JEL code: I12, M31